THE STATUTE OF THE CITY AND THE MASTER PLAN: INSTRUMENTS FOR SUSTAINABLE CITIES - Garcez, Gabriela Soldano; Carmello, Mariana Vicente Braga (PANORAMA OF BRAZILIAN LAW, 2015)
The Master Plan is an important instrument to promote significant changes in Brazilian cities in order to achieve a sustainable development and create a new relationship between man and the environment. As far as this planning is concerned, the Master Plan is a basic tool to stablish guidelines to meet citizens necessities, as well as quality of life and social-economic development. For this purpose, citizens supervision and participation in local activities are necessary, so that Constitutional principles and democracy are accomplished. Civil society should be part of the decision-making process concerning enviromental public policies, as well as integrate elaboration, and supervision of these policies, taking into consideration that the public authorities, as well as the society, have to protect and defend the environment for the future generations (article 225, of the Federal Constitution). In this context, this task aims, firstly, evaluare the general guidelines od the Statute of the City (Law nº 10.257/01) and the importance of the Master Plans. Afterwards, adresses the participatory management as a way of implementing the sustainable cities.